Hybrid warfare management of the United Kingdom - Mirković, Vladan M. (NBP. Nauka, bezbednosti, policija, 2023)
The United Kingdom achieves national security by acting in accordance with the "Fusion Doctrine", as a new approach to national security that should ensure the integration of all resources of national power. The Fusion Doctrine was officially accepted in 2021 in the new national security strategy. The new strategy integrated defense, security and foreign policies into a single act which reflects the Fusion Doctrine in the best manner. The new approach to security led to organizational changes of the entire state administration system, as well as within individual departments. Special emphasis was placed on the efficient coordination of the complex state apparatus.